Exploring the Components of a Culturally Responsive Faculty Development Program - China Jenkins (Adult Education Research Conference, 2017)
In this session, the presenter explores the existing literature to examine the components of a culturally responsive faculty development program.
Keywords: Culturally Responsive; Faculty Development